Hopf bifurcation analysis in a neutral predator–prey model with age structure in prey - Daifeng Duan; Qiuhua Fan; Yuxiao Guo (Electronic Journal of Qualitative Theory of Differential Equations, 2019)
We show a detailed study on the dynamics of a neutral delay differential population model with age structure in the prey species. By selecting the mature delay as a bifurcation parameter, we obtain the stability and Hopf bifurcations of the coexistence equilibrium. Moreover, by computing the normal form on the center manifold, we give the formulas determining the stability of periodic solutions and the direction of Hopf bifurcation. Finally, we give some numerical simulations to support and strengthen the theoretical results.